2021
DOI: 10.1111/jocn.16171
|View full text |Cite
|
Sign up to set email alerts
|

Effect of deep breathing exercise with Triflo on dyspnoea, anxiety and quality of life in patients receiving covid‐19 treatment: A randomized controlled trial

Abstract: Aims and objectives Determination of the effect of deep breathing exercise applied with Triflo on dyspnoea, anxiety and quality of life in patients who are hospitalized for COVID‐19 and have dyspnoea. Backround COVID‐19 is a viral infection that can cause severe pulmonary disease. Deep breathing exercise with Triflo in patients with COVID‐19 may contribute to the reduction/elimination of dyspnoea and anxiety, and improvement of respiratory and quality of life. Design The study was a randomized controlled clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 58 publications
0
22
0
1
Order By: Relevance
“…Most of the studies had been conducted in China ( n = 15) ( 30 , 33 , 34 , 45 , 50 , 52–55 , 63 , 64 , 66–69 ), Iran ( n = 6) ( 38 , 47 , 48 , 58 , 61 , 62 ), Italy ( n = 5) ( 29 , 31 , 41 , 44 , 57 ), India ( n = 4) ( 36 , 46 , 56 , 59 ), United States ( n = 2) ( 28 , 35 ), and Korea ( n = 2) ( 49 , 65 ). The remaining studies had been developed in Saudi Arabia ( n = 1) ( 27 ), Nigeria ( n = 1) ( 32 ), Indonesia ( n = 1) ( 39 ), France ( n = 1) ( 42 ), Turkey ( n = 1) ( 43 ), Thailand ( n = 1) ( 51 ), Latvia ( n = 1) ( 40 ), Ghana ( n = 1) ( 37 ), and Poland ( n = 1) ( 60 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies had been conducted in China ( n = 15) ( 30 , 33 , 34 , 45 , 50 , 52–55 , 63 , 64 , 66–69 ), Iran ( n = 6) ( 38 , 47 , 48 , 58 , 61 , 62 ), Italy ( n = 5) ( 29 , 31 , 41 , 44 , 57 ), India ( n = 4) ( 36 , 46 , 56 , 59 ), United States ( n = 2) ( 28 , 35 ), and Korea ( n = 2) ( 49 , 65 ). The remaining studies had been developed in Saudi Arabia ( n = 1) ( 27 ), Nigeria ( n = 1) ( 32 ), Indonesia ( n = 1) ( 39 ), France ( n = 1) ( 42 ), Turkey ( n = 1) ( 43 ), Thailand ( n = 1) ( 51 ), Latvia ( n = 1) ( 40 ), Ghana ( n = 1) ( 37 ), and Poland ( n = 1) ( 60 ).…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, there were insufficient data related to the evaluation of these interventions. A recent small randomized controlled study in patients with Covid‐19 has shown that deep breathing exercise led to statistically significant shorter hospitalization, higher Sp0 2 levels and higher quality of life compared to usual care without respiratory physiotherapy (Oner Cengiz et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Effectiveness of respiratory physiotherapy treatment in patients admitted to ICU, has been demonstrated in some reviews (Tipping et al, 2017;Bernal-Utrera et al, 2021). In that deep breathing exercise led to statistically significant shorter hospitalization, higher Sp0 2 levels and higher quality of life compared to usual care without respiratory physiotherapy (Oner Cengiz et al, 2022).…”
Section: Allmentioning
confidence: 99%
“…Перспективным методов видится дыхательная БОС, которая, считывая дыхательные движения, преобразовывает их в звуковые или визуальные сигналы, что облегчает контроль дыхания и осуществление техник респираторной реабилитации [77]. Исследования предполагают, что диафрагмальное дыхание БОС столь же эффективно, как и пропранолол, в облегчении мигренозных головных болей [78].…”
Section: механотерапия с биологической обратной связью в медицинской ...unclassified